PATOGENISITAS NEMATODA ENTOMOPATOGEN Steinernema spp. DAN Heterorhabditis spp. TERHADAP HAMA BAWANG MERAH Spodoptera exigua Hubner. - M. Hasyam Ashari; Johanis Panggeso; Burhanuddin Nasir (Universitas Tadulako, 2013)
The purpose of this study was to determine the pathogenicity (Lethal Concentrate = LC 50 value) of entomopathogenic Steinernema spp. and Heterorhabditis spp. nematodes against caterpillar pests of onion S. exiqua. This study was conducted during October to December 2013, in the Pests and Plant Diseases Laboratory, Agriculture Faculty, Tadulako University of Palu. This researchused a Completely Randomized Design (CRD) in atwo factorial experiment. The factors were type of nematodes and concentration. Each treatment was replicated three times, so that there were 24 experimental units. The nematodes used in this study were third in star nematodes. The concentration of the nematodes use dincluding 500 IJ per 4ml water (p1), 750 IJ per 4 ml water (p2), 1000 IJ per 4 ml water (p3)and 1250 IJ per 4 ml water (p4). The results showed that the mortality of S. exiqua larvae increases with rising nematod concentration. Highest mortality found during one day after application (DAA) to 6 DAA was under 1250 IJ (p4) so it is the most effective and efficient concentration to be implemented for controlling S. exiqua larvae. The estimated value of LC 50 using probit analysis is 425.64 IJ ml-1 water with the range of 244.77 to 740.16 IJ ml-1 water, in this case about 425- IJ ml-1 water is required to halve the number of the tested insects within six days. Key Words : Heterorhabditis spp, pathogenicity. Spodoptera exiqua H., and Steinernema spp nematodes.